1989
DOI: 10.1203/00006450-198911000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Release of Immunoreactive Growth Hormone-Releasing Hormone and Growth Hormone in Normal Children

Abstract: ABSTRACT. To evaluate the role of growth hormonereleasing hormone (GHRH) in the physiologic release of growth hormone (GH) we studied the nocturnal secretion of immunoreactive GHRH (ir-GHRH) and its relationship to GH release and various stages of sleep in six prepubertal (three boys) and six pubertal children (two boys) with normal stature. Their ages ranged from 8.1 to 14.9 yr and their bone ages from 6.8 to 14.8 yr. Blood was withdrawn continuously between 2200-0600 h at a constant rate of 5 mL/20 min. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…There was also a positive correlation between the basal ir-GHRH concentrations and the stage of puberty. This is in agreement with previous findings by our group that the number of nocturnal ir-GHRH pulses and the ir-GHRH amplitude in the peripheral circulation increase in puberty [31]. Argente et al [1] have also shown that pubertal children have higher basal ir-GHRH levels than prepubertal children and suggested that the dramatic rise in plasma GHRH concentrations during puberty indicates a role for this peptide in the adolescent growth spurt.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…There was also a positive correlation between the basal ir-GHRH concentrations and the stage of puberty. This is in agreement with previous findings by our group that the number of nocturnal ir-GHRH pulses and the ir-GHRH amplitude in the peripheral circulation increase in puberty [31]. Argente et al [1] have also shown that pubertal children have higher basal ir-GHRH levels than prepubertal children and suggested that the dramatic rise in plasma GHRH concentrations during puberty indicates a role for this peptide in the adolescent growth spurt.…”
Section: Discussionsupporting
confidence: 85%
“…Changes in circulating ir-GHRH concentrations have also been claimed to correlate with the secretion of GH [21,24], suggesting that peripheral plasma ir-GHRH measurement reflects hypothalamic function. Our own results also support the view that a considerable proportion of human peripheral ir-GHRH is derived from hypothalamus, since nocturnal ir-GHRH and GH peaks show a close temporal relationship [31].…”
Section: Discussionsupporting
confidence: 65%
“…Some groups have concluded that puberty had no effect on GH secretion (3,4). Some groups have concluded that puberty had no effect on GH secretion (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…The major secretory burst of GH secretion generally appears within 120 minutes after the JOURNAL 16 , during the first phase of slow wave · > 17 sleep ' , and correction of sleep abnormalities (especially those related to REM sleep) is associated with normalization of GH secretory patterns 18 . Patterns of GH secretion (and that of sleep onset) are themselves under genetic control 3 .…”
Section: Spontaneous Gh Secretionmentioning
confidence: 99%